ANALYSIS OF TAXPAYER ANNUAL REPORTING OF TAXPAYER MANUALLY TO THE TAX REVENUE TARGET IN BULELENG REGENCY - I Gusti Ayu Purnamawati; dwi arini nursansiwi (Universitas Pendidikan Ganesha, 2018)
This study aims to determine the analysis of taxpayer annual reporting of taxpayer manually to the target of tax revenue in Buleleng regency in 2015. The data used are qualitative data in the form of the number of mandatory taxpayers required SPT and the realization of tax returns. Data collection techniques used are interview and documentation method which is analyzed by using qualitative descriptive analysis. The results showed: the number of annual SPT reporting targets with the realization of annual SPT receipts has exceeded the target so that it can be said has been achieved. Factors that influence the achievement of tax revenue target in Buleleng Regency in 2015 is taxpayer compliance in conducting annual SPT reporting.